Indigenous flora of Western Himalayas - Thakur, Priyanka (Indian Horticulture, 2019)
The naturally occurring flora in a particular region or time refers to Indigenous Flora. The Indian flora represents nearly 12% of the global floral diversity and comprises four biodiversity hot spots in four phytogeographical regions, viz. the Himalayas, Western Ghats, North East India, and Andaman and Nicobar Islands. The number of plant species in the Himalaya is estimated at 25,000 i.e. 10% of the world’s known species and 50% of India’s endemic flora. This includes 7,020 species of fungi, 1,159 species of lichen and 2,000 species of bryophytes (including mosses and worts) with remainder ferns, angiosperms (flowering plants) and other species (http://www.greathimalaynnationalpark. org). A total of 10,503 species representing 240 families and 2,322 genera are reported plant diversity in the Himalayas, out of which number of recorded species in Uttrakhand (4,990), Himachal Pradesh (3,324) and Jammu and Kashmir (2,118) and remaining in Bhutan, Nepal and Arunachal Pradesh.